2002
DOI: 10.1007/s00268-002-6271-2
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Administration of Very High Dose of a‐Tocopherol Protects Liver from Severe Ischemia/Reperfusion Injury

Abstract: The effect of intramuscular administration of high (30 mg/kg body weight for 3 days) or very high (300 mg/kg body weight for 3 days) doses of a-tocopherol to Wistar rats subjected to total severe warm hepatic ischemia and reperfusion was investigated. After a 60-minute period of total hepatic ischemia and 120 minutes of reperfusion, animals were killed, and liver samples were taken for determination of malondialdehyde (MDA) and histological examinations. Blood samples were also taken for assay of serum a-tocop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 24 publications
(19 reference statements)
2
35
0
2
Order By: Relevance
“…The end production of lipid peroxidation includes aldehydes, hydrocarbon gases, and MDA. MDA is a sensitive index of lipid peroxidation [18,41] . Bertelli et al [33] suggested that MDA formation was reduced in the ischemic-reperfused myocardium of resveratrol-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The end production of lipid peroxidation includes aldehydes, hydrocarbon gases, and MDA. MDA is a sensitive index of lipid peroxidation [18,41] . Bertelli et al [33] suggested that MDA formation was reduced in the ischemic-reperfused myocardium of resveratrol-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…ble antioxidant in biological systems and has been proven effective in reducing oxidative stress and hepatocellular damage in both clinical and preclinical trials in doses from 10 to 300 mg/kg. 27,31,32 Ascorbic acid is a water-soluble antioxidant known to reduce oxidative stress with maximal hepatoprotective effects at a dose of 100 mg/kg. [28][29][30] Therefore, we examined the effects of ␣-tocopherol (300 mg/kg) and ascorbic acid (100 mg/kg) on GSH levels, early hepatocellular damage, late tissue necrosis, apoptosis, and accelerated tumor growth.…”
Section: I/r Accelerates the Local Outgrowth Of Preestablished Liver mentioning
confidence: 99%
“…[17][18][19] These include alternative clamping techniques such as ischemic preconditioning 8,[20][21][22][23] and intermittent clamping [24][25][26] as well as pharmacological intervention with antioxidants such as ␣-tocopherol and ascorbic acid. [27][28][29][30][31][32] We evaluated whether those strategies cross-protect the liver against (accelerated) outgrowth of micrometastases in this model.…”
mentioning
confidence: 99%
“…The intestinal mucosal atrophy also may be the result of high NO levels. Recent reports [52][53][54] suggest a wide range of intramuscular dose administration schemes for ␣ -tocopherol (up to 500 mg/kg), but in a Medline search, we could not fi nd any dose-dependent toxicity of ␣ -tocopherol. Therefore, the cytoprotective-antioxidant dose of ␣ -tocopherol is yet to be defi ned.…”
Section: Discussionmentioning
confidence: 83%